Diagnostic Accuracy of Fact in Clinically Suspected Cases of Acute Appendicitis in Adolescents and Adults, Taking Surgical Findings as Gold Standard - Hira Ashfaq Butt, Rukhsana Nasim, Khalid Javed, Fareeha Shahid, Nosheen Kanwal, Huda Fazli, Islah Ud Din (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: to evaluate the diagnostic accuracy of FACT in clinically suspected cases of Acute Appendicitis in adolescents and adults, taking surgical findings as gold standard. Methods: A total of 335 patients referred from emergency department with clinical suspicion of acute appendicitis were enrolled at Radiology Department, Services Hospital Lahore, from April, 2016 to October, 2016. FACT was performed using multi-slice CT. The cases underwent surgery and the results were recorded. The results of Focused Abdominal Computed Tomography and surgery were compared taking surgical findings as gold standard. Results: The mean age of patients in our study was 23.01 ± 5.479. We found 278 true-positives, 50 true-negatives, 04 false-negatives results, with sensitivity of 98.6%, a specificity of 94.3%, a PPV of 98.9%, a NPV of 92.6%, and an accuracy of 98%. An alternate diagnosis was made by FACT in 40 patients (11.9%). Conclusion: FACT (focused non-enhanced abdominal computed tomography) is a highly accurate imaging modality for diagnosis of acute appendicitis in adolescents and adults. Keywords: Focused Abdominal CT, Acute Appendicitis, FACT, Diagnostic Acuuracy